2014
DOI: 10.1186/1471-2458-14-199
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing social and health outcomes after motor vehicle crash injury: an inception cohort study protocol

Abstract: BackgroundThere is growing evidence that health and social outcomes following motor vehicle crash injury are related to cognitive and emotional responses of the injured individual, as well as relationships between the injured individual and the compensation systems with which they interact. As most of this evidence comes from other states in Australia or overseas, investigation is therefore warranted to identify the key determinants of health and social outcomes following injury in the context of the New South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Study methodology has been previously reported. 12,19 Briefly, inclusion study criteria were: a) injury due to crash involving a motorized vehicle on land (public/private road/driveway/parking space…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Study methodology has been previously reported. 12,19 Briefly, inclusion study criteria were: a) injury due to crash involving a motorized vehicle on land (public/private road/driveway/parking space…”
Section: Study Populationmentioning
confidence: 99%
“…severe traumatic brain injury, spinal cord injury, extensive burns or multiple amputations), as these injuries are not covered by the CTP scheme in NSW; and d) isolated mild/moderate soft tissue injuries such as bruises, abrasions or cuts. 19 From the study sites (emergency departments, general practitioners, physiotherapy clinics, police crash records and the claims database of a government insurance regulator), data for potential eligible participants were entered on a secure online platform, here called Research electronic data capture (REDCap). 15 Once screened, potential participants were sent a letter that detailed the purpose of the study, what was involved and inviting them to participate in the study.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This study was a sub-study of the larger Factors In uencing Social and Health Outcomes following road transport injury quantitative inception cohort study (the FISH study) [28] . The FISH study cohort consists of people (aged 17+ years) who sustain a physical road tra c injury (RTI) (car occupant, motorcyclist, pedestrian, and bicyclist) in the state of New South Wales (NSW), Australia who have been recruited within one month of injury [28] . The study excludes severe and catastrophic injuries (such as severe traumatic brain injury, spinal cord injury, amputations and severe burns).…”
Section: Methods Participants and Settingmentioning
confidence: 99%
“…This study was a sub-study of the larger Factors Influencing Social and Health Outcomes following road transport injury inception cohort study (the FISH study) [25] . The FISH study cohort consists of people (aged 17 + years) who sustain mild to moderate severity road transport injury (car occupant, motorcyclist, pedestrian, and bicyclist) in the state of New South Wales (NSW), Australia who have been recruited within one month of injury [25] .…”
Section: Participants and Settingmentioning
confidence: 99%